Analysis of the Spirituality Construct in Measuring Student Self-Resilience - Ayong; Najlatun Naqiyah; Ari Khusumadewi; Ahmad Rofi Suryahadikusumah; Irfan Fahriza (Bisma The Journal of Counseling, 2025)
Spirituality is a personal factor that plays an important role in strengthening students’ self-resilience; however, it has not yet been comprehensively accommodated in existing resilience measurement instruments. This issue highlights the need for an in-depth examination of spirituality constructs that are relevant to self-resilience. This study aims to analyze and synthesize the spirituality construct in measuring student self-resilience based on a systematic review of relevant literature. A systematic literature study was employed by collecting data through searches of academic publications using the keywords “spirituality,” “spiritual well-being,” “meaning in life,” and “transcendence.” The data were analyzed using critical content analysis of seven key relevant publications. The results indicate that the most frequently referenced instruments for measuring spirituality related to self-resilience include the Religious and Spiritual Struggles (RSS), Daily Spiritual Experiences Scale (DSES), NIH-HEALS, and a questionnaire developed by Shelton et al. Further analysis identified four main dimensions of spirituality in self-resilience: connection, inner peace and harmony, meaning and purpose of life, and spirituality practice as coping. The findings conclude that spirituality constructs provide strong conceptual contributions to strengthening student self-resilience measurement. The implications of this study support the development of spirituality-based assessment instruments and intervention programs within educational and counselling contexts.